Actualization of the Community-Based Total Sanitation Program (Free from Open Defecation) in Realizing the Target of Bandung City 100% Open Defecation Free - Oneng Purnamasari (GoResearch - Research & Publishing House, 2022)
The realization of the target of the City of Bandung Open Defecation Free (SBS) initiated by the Health Service is targeted for completion in early 2023. So this research is aimed at analyzing the actualization of the program related to whether or not it will achieve the predetermined target. In the study, the researcher relies on the use of the program actualization model from David C. Korten (1980) to analyze the suitability between the program and the implementing agency through indicators (1) Governance Clarity; (2) Physical Ability; and (3) Social Ability. This study uses a qualitative descriptive method with data collection techniques through observation, documentation studies, and interviews. The results of the study revealed that the actualization of related programs had not run optimally because 1 (one) of the 3 (three) indicators did not meet the required criteria so that technical improvements were needed in terms of rules and involvement so that the actualization of the program could reach the target on time.